Using stable isotopes to understand relative contributions of evaporation and evapotranspiration on groundwater recharge in the Verlorenvlei catchment, west coast, South Africa - Mafilika, Siyabulela Ben (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.